Kata – The true essence of Budo martial arts? - Dodd, Simon Alexander; Brown, David (Revista de Artes Marciales Asiáticas, 2016)
This paper uses documentary research techniques to analyse the use of kata, forms, in the Japanese martial arts. Following an introduction on the existence of kata practice, using existing sources of information the paper first examines the spiritual developments of bushido, secondly, the social changes that led to the redevelopment of bujutsu into budo is scrutinsised. Next, the position of kata in relation to budo martial arts is explored followed by a discussion on the use of kata as a pedagogy. Finally, kata is repositioned in light of the contextual expansion investigated demonstrating how kata could represent the intended essence of budo as well a culturally-valued, spiritual pedagogy.